Pengaruh Pelatihan Berbasis 3S ( SDKI , SLKI , SIKI ) Terhadap Pengetahuan Perawat Tentang Pendokumentasian Asuhan Keperawatan Praktik Mandiri - Emi Eliya Astutik; M. Elyas Arif Budiman; Prestasianita Putri; Achmad Efrizal Amrullah (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction:The documentation is a comprehensive record of the patient’s condition and can be used as evidence of accountability. In Indonesia, many nurse do not document nursing orphanage properly. Implementation of nursing documentation is due to various factors, one which is knowledge. One of factor in improving the knowledge of nurses in documenting nursing orphanages is through training Objectives: This study aims to find out the impact of 3S based training (SDKI, SLKI, SIKI) on nurses knowledge of documentation of nursing care independent practice Methods: The method used is quantitative research, pre-esperimental research design with one-group pretest-posttest research design using Wilcoxon test. The population used in this research was 54 independent practice nurses from DPK PPNI Tanggul. The sample for this research consisted of 15 respondents who had been selected using purposive sampling in accordance with the inclusion criteria, namely nurses who were present and committed to participating in the training and mentoring process. Results:In the study showed before given training , knowledge of nurses category good is 2 respondents (13.3%). After conducting the training , knowledge of nurse category good as 11 respondents (73.33%). The Wilcoxon test results obtained a p-value of 0.003 ≤ 0.05 which means there is a difference between the pre-test and post- test results Conclusions: The importance of training for nurses is to increase their knowledge in nursing documentation, so that nurses are expected to be able to implement related nursing documentation.